Synthesis Of Blood-Brain Barrier Permeable Aurones As Modulators Of Microglia - Chia, Shi Yi (2023)
In the present study, a series of aurones incorporating basic amines and lipophilic functionalities at ring A and/or ring B were synthesized to improve upon present sulfuretin activity towards targeting brain microglia while overcoming the blood-brain barrier. The effects of the synthesized aurones on LPS-stimulated BV-2 microglial cells were examined and their modulation to an activated M1 phenotype and alternatively activated M2 phenotype were characterized. Also, the BBB permeability of the aurones were determined using the parallel artificial membrane permeability assay for blood-brain barrier (PAMPA-BBB) model. The results revealed that several aurones showing significant inhibitory activities against nitric oxide (NO) levels of more than 50% at 1 to 10 μM (p < 0.01 versus control).